Self-evaluation affective and social grounds of intentionality - Konzelmann Ziv, Anita; Lehrer, Keith; Schmid, Hans Bernhard (Springer eBooks., 2011)
This volume examines the affective and social dimensions of self-related activities. This is a novel way of approaching traditional questions such as the scope and purpose of self-knowledge, the interrelation between the social and the individual person, and the significance of emotional appraisal. Focusing on self-evaluation instead of self-knowledge in shifting from a doxastic to an axiological perspective. The scientific added value created by this approach is threefold: i) it opens up a broadr perspective on the structure of self-reflection which includes a matrix of values; ii) as valauations imply a social contaxt, it extends to social relations; iii) since affective attitudes are crucial for the recognition of values, it incorparates feelings and emotions. In short, self-evaluation is a conception of self-refelection which includes sociality and affectivity. This volume contains contributions by leading figures in philosophy of mind and action, emotion theory, and phenomenology. It allows a global view on the most recent reflections on the subject matter, being of interest for professional philosophers, as well as for researchers from various neighboring disciplines.